Teaching students about their own modality strengths can lead to positive learning outcomes. Issue 2 (2nd July 2016) - Winebrenner, Susan
ABSTRACT: A recent study by Lodge, Hansen, and Cottrell (2016) was brought to the attention of the author of this commentary and motivated her to communicate this rebuttal regarding some of the suggested conclusions. The negative results for certain students of changing current classroom practices which have been noticeably successful for them in improving their mastery and testing results seems careless at best without further studies that seek to verify the presence of better outcomes for some students who use modality based strategies. The study authors describe an alternative position which suggests that modality effects are more task dependent, than dependent of the pedagogical choices of individual students. Based on the commentary author's clinical evidence from large numbers of teachers who have found improving school success for some students using modality based strategies, the commentary cautions that educators must be very careful before abandoning teaching and learning strategies that lead to more positive learning outcomes for some students. Perhaps a meeting of the minds could occur if the concepts of "equipping" students with details of various strategy alternative from which they could choose when their present methods are not successful would be more reasonable, rather than making it the teacher's responsibility to "prescribe" specific strategies for individual students.